Descriptive Analysis of Writing Composition from the Ideas to the Paragraph - Nurrohmah, Titik (Register Journal, 2008)
What are the ways to discover the ideas to write? How to organize the ideas into the paragraph? To answer these questions, the writer conducted a qualitative research that the object of the research is writing composition on the discovering the ideas and organize it into paragraph. The writer used descriptive method. For obtaining the data, the writer used library method as the instrument and used secondary sources that constituted secondhand information, such as reference book. Meanwhile, in analyzing the data, the writer used an expository writing. There were several ways in discovering ideas as the result of this study. Those included remembering experience, getting people opinion about particular subject by giving evidence, finding a great deal by asking other people about their experience and going to the library to get any ideas. Whereas, to organize the ideas into paragraph, someone has to do some steps, such as selecting a subject, planning a composition and making an outline.Keywords: Writing Composition; Idea;Â  Paragraph